전분함량이 높은 콩 유전자원 선발 - 구성철(Sung Cheol Koo); 전명기(Myeong Gi Jeon); 이영훈(Young Hoon Lee); 김현영(Hyun-Young Kim); 강범규(Beom Kyu Kang); 고종민(Jong Min Go); 백인열(In Youl Baek); 윤홍태(Hong Tai Yun); 최만수(Man Soo Choi) (Korean journal of breeding, 2014)
본 연구는 고 전분 함유 유용 유전자원 선발 및 콩 우량품종 육성의 기초자료로 활용하고자 국내 콩 주요 품종 및 보존 유전자원의 전분함량과 변이 양상을 분석하였으며 그 결과는 다음과 같다. 1.총 2354점 국내 콩 주요 품종 및 보존 유전자원에 대한 요오드-전분 반응에 의한 착색 정도에 따라 1에서 4등급으로 분류를 하였으며, 대부분의 콩 유전자원이 2∼3등급으로 분류되었고, 가장 강한 착색 반응을 보인 4등급으로 126점의 유전자원이 선발되었다2.전분함량의 정량적 분석을 수행한 결과, 1, 2등급으로 분류된 유전자원 Daewang, Soheonje, Jyuiku #109는 각각 0.57, 0.45, 0.54%의 낮은 전분함량을 나타내었다. 반면, 4등급으로 분류된 유전자원은 2.81∼4.55%의 상대적으로 높은 전분함량을 보여 요오드-전분 반응법은 유전자원의 대량검정에 유용하게 이용할 수 있을 것으로 판단되었다.3.각 유전자원에서 전분함량의 차이가 다른 구성 성분의 함량에 영향을 미치는지를 알아보기 위해, 조단백질함량, 조지방함량, 수분함량을 각각 측정하였다. 전분함량의 변화는 조단백질 함량 변화에 영향을 미치며, 조지방과 수분함량의 변화에 영향이 없음을 확인하였다. Starch is the most important carbohydrate in the human and animal diets and it also has numerous industrial applications. Starch is widely used as a key material for processed foods such as bread, pancakes, cereals, noodles, pasta, porridge and tortilla. Increasing the starch content in food crops is one of the important targets for crop breeding. We used a starch-iodine test to identify varieties with high starch content in 2354 soybean germplasm collection and found a total of 126 germplasm that showed a strongly positive reaction. We quantified starch content from highly stained 7 soybean accessions by standard method (glucose-oxidase). As results, starch contents of 7 soybean germplasm were 2.81∼4.55%, whereas the weakly stained controls showed low starch content with less than 1%. We also measured the contents of protein, fatty acid, water potential and free sugar in 7 soybean germplasm with high starch content. High starch germplasm showed lower protein content, while low starch germplasm showed higher protein content. Our results suggest that the increasing of starch content could affect protein level in soybean seed.